Influence of Pasteurella multocida Toxin on the differentiation of dendritic cells into osteoclasts - Chakraborty, Sushmita; Handrick, Bianca; Schmidt, Silke; Eigenbrod, Tatjana; Hieke-Kubatzky, Katharina (Immunobiology, 2018)
Dendritic cells (DC) are antigen-presenting cells that connect the innate and adaptive immune system to ensure an efficient immune response during the course of an infection. Recently, DC came into the spotlight as a potential source of osteoclast progenitors, especially under (auto)inflammatory conditions. The virulence factor Pasteurella multocida Toxin (PMT) causes atrophic rhinitis in pigs, a disease characterised by a severe reduction of nasal bone. Our group and others have shown the potential of PMT in mediating differentiation of monocytes/macrophages into bone-resorbing osteoclasts. However, whether DC are target cells for PMT-induced osteoclast differentiation, is currently unknown. Using different murine DC model systems, we investigated the ability of PMT to induce osteoclast formation in DC. Similar to our previous observations in macrophages, PMT was endocytosed by DC and triggered intracellular deamidation of residue Q209 of the Gq alpha subunit. Still, PMT failed to induce prolonged secretion of osteoclastogenic cytokines and osteoclast formation; instead PMT-treated DC secreted interleukin-12 (IL-12), an inhibitor of osteoclastogenesis. In this study, we show that in comparison to bone marrow-derived macrophages, PMT induces maturation of DC through increased expression of the activation markers CD80 and CD86. As maturation of DC prevents their transdifferentiation into osteoclasts, we hypothesize that PMT, a potent osteoclastogenic toxin, fails to trigger osteoclastogenesis in DC due to its effect on DC maturation and IL-12 production.